Introduction of Google My Business for the Utilization of Digital Marketing in the Era of E-Commerce & Social Media - prasetyo dono saputro (LPPM Universitas Putera Batam, 2020)
In the era of the industrial revolution 4.0 and increasingly incessant to become a society 5.0, SUBCOMTECH held a training & workshop on the use of technology at Ciputra World Surabaya Mall with technology training materials. One of the material is